Analisis Kinerja Protokol Routing Reaktif dan Proaktif pada MANET Menggunakan NS2 - Alamsyah; Eko Setijadi; I Ketut Eddy Purnama; Mauridhi Hery Purnomo (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
The development of mobile ad-hoc network (MANET) is becoming popular and interesting to research because it has a fast characteristic, cost-effective deployment, able to manage topology change independently, and can be applied to emergency locations such as forest fire detection, military operation, and health monitoring. However, the problems faced by MANET are dynamic network topology changes, limited energy consumption, and without the support of existing infrastructure. In order to overcome dynamic topology changes and to obtain reliable network quality, then routing protocol selection is critical in designing MANET. This study aims to analyze the performance of AODV, DSR, DSDV, and OLSR routing protocols based on the quality of service (QoS). Scenarios based on the number of vertices, packet size, a broad area of simulation, length of simulation, simulation speed, mobility model, and propagation model. The simulation has been done to produce four graphs, each of which describes the PDR, throughput, packet loss, and delay. The simulation results show that OLSR performs better than DSR, AODV, and DSDV in terms PDR, throughput, packet loss, and delay. OLSR average value in PDR by 39.997%, throughput by 417.383 Kbps, packet loss by 60.003%, and delay of 15.52 milliseconds.